Developing a peer supported feedback model that enhances oral proficiency in French - Bedford, Simon; Bissoonauth, Anu; James, Klem; Stace, Ray (Journal of University Teaching and Learning Practice, 2020)
This article investigates the process of development for a novel online peer-supported approach that enhances oral proficiency in French at an Australian university to cope with ever more complex challenges. These challenges include students with mixed ability in the same class, reduced teaching resources and student surveys identifying a lack of speaking practice affecting confidence and performance in oral assessments. A related aim of the present study was to facilitate assessment literacy of our students by encouraging them to make links between the skills practised in class and the requirements for the final oral summative assessment. Methodology draws on educational practice influenced by a social constructivist approach to develop a learning model using online peer feedback, where more advanced learners support less experienced peers outside the formal classroom. Preliminary results reveal that although the model was deemed to be ‘generally effective’ in enhancing speaking skills and developing a better understanding of assessment literacy, it needs to enable learners to build their meta-skills across the three-year degree program to be truly effective. The conclusion explores further development and expansion of the learning approach across the French undergraduate program and makes future recommendations.